Effect of dapagliflozin as an adjunct to insulin over 52 weeks in individuals with type 1 diabetes: post-hoc renal analysis of the DEPICT randomised controlled trials. Issue 10 (October 2020) - Groop, Per-Henrik; Dandona, Paresh; Phillip, Moshe; Gillard, Pieter; Edelman, Steven; Jendle, Johan; Xu, John; Scheerer, Markus F; Thoren, Fredrik; Iqbal, Nayyar; Repetto, Enrico; Mathieu, Chantal
Summary: Background: The DEPICT-1 and DEPICT-2 studies showed that dapagliflozin as an adjunct to insulin in individuals with inadequately controlled type 1 diabetes improved glycaemic control and bodyweight, without increase in risk of hypoglycaemia. We aimed to determine the effect of dapagliflozin on urinary albumin-to-creatinine ratio (UACR) and estimated glomerular filtration rate (eGFR) using pooled data from the DEPICT studies. Methods: In this post-hoc analysis, we used data pooled from both DEPICT studies (DEPICT-1 ran from Nov 11, 2014, to Aug 25, 2017; DEPICT-2 ran from July 8, 2015, to April 18, 2018), in which participants were aged 18–75 years, with inadequately controlled type 1 diabetes and with a baseline UACR of at least 30 mg/g. In the DEPICT studies, participants were randomly assigned (1:1:1) to receive dapagliflozin (5 mg or 10 mg) or placebo all plus insulin, for 24 weeks, with a 28-week long-term extension (ie, 52 weeks in total). In this post-hoc analysis, we assessed the percentage change from baseline in UACR and in eGFR, up to 52 weeks. UACR, eGFR, and safety were assessed in all eligible participants who had received at least one dose of study drug. HbA1c, bodyweight, and systolic blood pressure were assessed in all participants who received at least one dose of study drug during the first 24-week period, and who had a baseline and any post-baseline assessment for that parameter. The DEPICT trials were registered with ClinicalTrials.gov, NCT02268214 (DEPICT-1), NCT02460978 (DEPICT-2), and are now complete. Results: 251 participants with albuminuria at baseline were included in this post-hoc analysis; of whom 80 (32%) had been randomly assigned to dapagliflozin 5 mg, 84 (33%) to dapagliflozin 10 mg, and 87 (35%) to placebo. Compared with placebo, treatment with both dapagliflozin doses improved UACR over 52 weeks. At week 52, mean difference in change from baseline versus placebo in UACR was −13·3% (95% CI −37·2 to 19·8) for dapagliflozin 5 mg and −31·1% (−49·9 to −5·2) for dapagliflozin 10 mg. No notable change from baseline was seen in eGFR, with a mean difference in change from baseline versus placebo of 3·27 mL/min per 1·73 m 2 (95% CI −0·92 to 7·45) for dapagliflozin 5 mg and 2·12 mL/min per 1·73 m 2 (–2·03 to 6·27) for dapagliflozin 10 mg. Similar proportions of participants in each treatment group had adverse events and serious adverse events, including hypoglycaemia and diabetic ketoacidosis; no new safety signals were identified in this population. Interpretation: Treatment with dapagliflozin resulted in UACR reduction, which might provide renoprotective benefits in individuals with type 1 diabetes and albuminuria. Dedicated prospective studies are needed to confirm these findings as prespecified endpoints. Funding: AstraZeneca.